The bungy "mechanic" as an aid to trampoline coaching - McClymont, D.; Burley, P. (coachesinfo.com, 1999)
This study describes the characteristics of an aerial 'mechanic' developed to utilise the rebound characteristics of bungy cord and used in the teaching of intermediate and advanced trampoline skills. An elite trampolinist was filmed while in the harness and take-off and landing velocities were derived at maximum tension and in free bouncing. Time in the air, and support during flight, were identified by the coach as positive characteristics of the system. Five athletes exposed to nine coaching sessions using the system commented positively.